Incorporating English Skills in Blended Learning During the COVID-19 Pandemic: A Narrative Inquiry - Wahyuningsih, Sri; Afandi, Muhamad (Elsya : Journal of English Language Studies, 2022)
The present study mainly attempts to explore the experiences of the two English language lecturers in incorporating English skills in blended learning during the COVID-19 pandemic and its effects on teaching professionalism considering that few studies discuss the ways of incorporating English skills in blended learning in more detail. To investigate the lecturers’ experiences, a narrative inquiry was employed in this study. Data were collected through narrative interviews with two English language lecturers at one of the Indonesian higher educations. The findings reveal that blended learning can be a better solution for learning activities amidst the COVID-19 pandemic. Regarding English skills incorporation in blended learning, it was found that the English lecturers used a number of ways of teaching English. First, creating a fun class in blended learning by using some applications like YouTube, video, Instagram, Facebook, and others in incorporating English skills. Second, asking students to have presentations and explain the materials. Third, reviewing books or observing videos. Fourth, providing games in the EFL classroom. Fifth, making use of digital technology and application in teaching English in blended learning such as Kahoot, Quizzes, Google Workspace, Jam board, Pear deck, and so on. Finally, the English lecturers are interested in making use of blended learning in incorporating English skills, particularly during this pandemic. Further, they intend to provide suitable materials for blended learning in EFL classrooms. The findings of this study have offered the need of developing professionalism among the English lecturers in implementing blended learning that can be realized by taking part in training on the application of blended learning and providing appropriate English materials in incorporating English skills for creating meaningful and successful learnings.